(untitled) (ES Review. Spanish Journal of English Studies, 2025)
Empathy plays a key role in Margaret Atwood’s The Blind Assassin (2000), a complex novel consisting primarily of the fictional memoir of Iris Chase, its eighty-two-year-old protagonist and first-person narrator. Working within the theoretical framework of Suzanne Keen’s research on narrative empathy, the aim of this article is twofold: to examine the representation of empathy in The Blind Assassin and to explore the capacity of the novel to encourage readerly empathy towards a character who is frank enough to acknowledge that she has not provided the emotional support expected from her, and bitterly regrets her destructive lack of affective empathy.